العلاقة المتبادلة بين المعرفة بالمفردات واستنتاج معانيها في الاستيعاب القرائي لدى متعلمي العربية لغة ثانية - Siti Aishah Rohani (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
Vocabulary knowledge is considered as an important aspect in reading comprehension. However, students often faced a problem when they encountered unknown words during reading. One of the strategy to overcome this problem is by using lexical inferencing strategy. Therefore, the researcher studied the association between vocabulary knowledge and lexical inferencing in reading comprehension among Arabic language students in IIUM. This research seeks to look for possibilities of co-relations between vocabulary knowledge and lexical inferencing in reading comprehension, statistically significant difference between male and female in vocabulary knowledge as well as between male and female in lexical inferencing. The respondents were 30 male and 30 female students. Each students were given two types of test to measure their vocabulary knowledge and lexical inferencing as a mean of data collection. Data were then analysed through Pearson correlation coefficient and T-test. The result identified that there is a positive relationship between vocabulary knowledge and lexical inferencing. However, no statistically significant difference can be found between male and female in both vocabulary knowledge and lexical inferencing